Fantastic Binomial, the Conceptual Image-making Method for Contemporary Free Verse - Naumenko, Nataliia (My University, 2010)
Metaphor as one of the conceptual tropes got a lot of subordinate conceits for its description throughout all the literary history. In the 20th century, one of them was thoroughly formulated in Gianni Rodari’s Grammar of Fantasy (La Grammatica della Fantasia) as a fantastic binomial, a clause which contains a noun and a verb (or an adjective) that a priori are not tied with logical ties and further set up a base for a fairy-tale story. This is the main difference of a fantastic binomial from a usual metaphor. In this paper, we confirmed the mentioned kind of metaphor as a conceptual image-making way in contemporary Ukrainian free verse.
Keywords: metaphor; fantasy; free verse; century Ukrainian poetry 20th; метафора; фантазія; вільний вірш; українська поезія ХХ століття; кафедра гуманітарних дисциплін; фантазия; свободный стих; украинская поэзия ХХ века